Changes In Community Consumption Patterns Due To The Covid-19 Pandemic - Andriani Andriani (STIE PGRI Dewantara Jombang, 2021)
The Covid-19 pandemic has changed people's consumption patterns. On the one hand, the community is required to sort out and choose needs that are on a priority scale. On the other hand, people want the needs of life to be fulfilled to the fullest. This research objects to analyze changes in community consumption patterns due to covid-19. This study uses a qualitative approach with a literature study method. The data used in this study are secondary, in the form of research from institutional data AND scientific journals both print and online which selected based on four aspects, namely: 1) Provenance; 2) Objectivity; 3) Persuasiveness; 4) Values. The results of the study SHOW THAT, in general, the poor are only able to meet their primary needs. The middle class almost fulfills all their needs, both primary, secondary, and tertiary needs. The upper class can meet all their needs, both primary and tertiary. The Covid-19 pandemic also changing society's consumption patterns from consumption habits to tending to realistic. The quantity of consumption is relatively constant but the quality is decreasing. The increase in consumption allocation is more on prioritizing food quality and food diversity. Additionally, a new trend for shopping is appearing online through certain marketplace, so there is a new trend in the form of utilization of digital wallets or other non-cash transactions.